Effect of a chitosan-based flame retardant with a caged structure on unsaturated polyester resin. Issue 8 (24th May 2022) - Jiang, Zicheng; Ma, Su; Zhang, Gang; Song, Dongdong; Wang, Yanlin; Lao, Fujing
ABSTRACT: A chitosan-based flame retardant with a caged structure, chitosan maleic acid mono (1-thio-phosa-4-hydroxymethyl-2, 6, 7-trioxa-bicyclic [2.2.2] octan-4-methylene) ester salt (CS-MA-SPEPA), was synthesized and characterized. Cone calorimeter (CC) results indicated that the introduction of CS-MA-SPEPA into an unsaturated polyester resin (UPR) matrix could effectively reduce the HRR, TRR, and SPR. More importantly, the incorporation of CS-MA-SPEPA suppressed the release of toxic gases (CO) from the UPR matrix. The char residues results implied that the combination of CS-MA-SPEPA into UPR increased the degree of graphitization of the matrix and made char residues intumescent and tight, which could efficiently block the exchange of oxygen and heat. Graphical abstract: uf0001